Isolated fetal echogenic bowel and iron-rich mineral water supplement: a case series and review of the literature. (4th July 2022) - Lavie, Anat; Reicher, Lee; Zohav, Eyal; Ram, Maya; Malovitz, Sharon
Abstract: Natural iron-rich mineral water (IRMW) is a supplement with a higher iron bioavailability than oral iron supplement tablets. Five (4%) of 116 women who consumed IRMW starting from 16 weeks of gestation were diagnosed as having isolated foetal echogenic bowel at a single community maternity clinic between 2012 and 2015. The workup of all the women was otherwise negative. Four women taking IRMW were re-checked after discontinuation of the supplement and had a normal-appearing foetal bowel. Our observations suggest that isolated echogenic bowel may be related to the consumption of IRMW, possibly due to the high absorption of iron, leading to the coating of the internal wall of the foetal bowel and subsequent appearance of an echogenic bowel. Although this finding appears free of harmful ramifications, its possible sonographic effects on the appearance of the foetal bowel should be considered in light of the increasing popularity of IRMW use. IMPACT STATEMENT: What is already known on this subject? IRMW is a highly absorbed iron supplement. The differential diagnosis for foetal echogenic bowel is broad and requires thorough investigation. Iron is secreted through the maternal blood to the amniotic fluid, which is swallowed by the foetus, reaching its bowel. What do the results of this study add? IRMW consumption is a possible aetiology of an isolated foetal echogenic bowel in the second half of pregnancy, conveying no risk of foetal morbidity or mortality. What are the implications of these findings for clinical practice and/or further research? In light of the increasing popularity of IRMW, we believe that it is important to increase the level of awareness of the possible effects of its intake on the sonographic appearance of the foetal bowel.